May Delegation Affect Firms' Ability to Collude? - Luca Lambertini; Marco Trombetta (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
In a model of repeated Cournot competition under complete information, we show that delegation has no effect on cartel stability if managers collude, while it may hinder cartel stability when owners collude in setting the incentive schemes. If owners can choose whether to delegate or keep control of their respective firms, and both groups of individuals collude or play noncooperatively in their respective variables according to the level of intertemporal discount factor, then if managers are not able to collude in output levels, owners' delegation decision is non-monotone in the discount factor.
Keywords: 330